2020
DOI: 10.1002/jbm.a.37018
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐loading three‐dimensional scaffolds based on hydroxyapatite‐sodium alginate for bone regeneration

Abstract: Bone tissue engineering is a promising approach for tackling clinical challenges. Osteoprogenitor cells, osteogenic factors, and osteoinductive/osteoconductive scaffolds are employed in bone tissue engineering. However, scaffold materials remain limited due to their source, low biocompatibility, and so on. In this study, a composite hydrogel scaffold composed of hydroxyapatite (HA) and sodium alginate (SA) was manufactured using three-dimensional printing. Naringin (NG) and calcitonin-generelated peptide (CGRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…In the presence of proteolytic enzymes, EGF is cleaved from the polypeptide and is progressively released from the scaffold. A constant and stable release over 3 weeks from an Alg/sodium hydroxyapatite hydrogel was observed for calcitonin-gene related peptide and naringin [171], while similar results were reported for the release of berberine from an Alg/calcium phosphate scaffold [172].…”
Section: Alginatesupporting
confidence: 80%
“…In the presence of proteolytic enzymes, EGF is cleaved from the polypeptide and is progressively released from the scaffold. A constant and stable release over 3 weeks from an Alg/sodium hydroxyapatite hydrogel was observed for calcitonin-gene related peptide and naringin [171], while similar results were reported for the release of berberine from an Alg/calcium phosphate scaffold [172].…”
Section: Alginatesupporting
confidence: 80%
“…Recent studies reported the effective use of SA/HA-based scaffolds as biomedical materials, in which they identified their possibility of use in bone defect repair [ 9 ], bone regeneration [ 31 ], and promotion of new cartilage generation [ 32 ]. As mentioned above, our study involved enhanced mechanical properties compared with others.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, neuropeptides and axonal guidance molecules that possess osteogenic effects have been incorporated into bone scaffolds to promote tissue regeneration. For example, CGRP was used as printing ink in the fabrication of scaffolds and displayed osteoinductive abilities in vivo [ 14 ]. However, incorporation of proteins into scaffolds creates problems such as short half-lives, high cost, rapid degradation, difficulty in disinfection and immunogenicity.…”
Section: Introductionmentioning
confidence: 99%